Psychometric Properties of the Turkish Version of "Inventory of Callous-Unemotional Traits-Youth Form" - Sezen Köse; Tuğba Kalyoncu; Berrin Eylen Özyurt; Burcu Özbaran (Galenos Yayinevi, 2017)
Aim: Callous and unemotional traits such as the inability to make emotional communication, and the lack of feelings of guilt and empathy are frequently found in the young with antisocial manners, who are at increased risk for violent behavior in the future. We aimed to identify the psychometric properties of the Turkish version of the "Inventory of Callous-Unemotional Traits-Youth Form" (ICU-TR). Materials and Methods: The ICU-TR was administered to 301 students, and only 250 completely filled out forms have been included in the study. One hundred students filled out the ICU-TR 3 weeks later for test-retest reliability. The factor structure of the scale has been studied with principle component analysis, and reliability measured with Cronbach's alpha. Pearson correlation is used for criterion-related validity and test-retest reliability. Results: The mean age of the cases was 14.38, with 68% male and 32% female. Factor analysis supported a two factorial structure. The first factor (callousness) had 12 items (Eigen value=4.8; r=0.58, p<0.001); the second factor (uncaring) had 11 items (Eigen value=2.3; r=0.64, p<0.001). Cronbach's alpha coefficient for the total scale was 0.55, 0.77 for the callousness subscale, and 0.58 for the uncaring subscale. Test-retest reliability coefficient was 0.88 (p<0.001). Conclusion: The construct validity of ICU-TR was shown by factor analysis. The result is that test-retest reliability, sub-scale and total scale reliability are all sufficient.